ICT ASSET MANAGEMENT SYSTEM FOR KEDAH STATE HEALTH DEPARTMENT - Suhailah, Mohamad Suhaib (Universiti Malaysia Sarawak (UNIMAS), 2019)
A web-based ICT Asset Management System for Kedah State Health Department is a system that record all the ICT asset such as personal computer, laptop, printer, server and many more that is used in Kedah State Health Department located in Alor Setar, Kedah. There are about six section and more than 20 Units in the building. All ICT asset must be recorded ill order to identify the asset that need to repair and whether the asset under which rental company there five rental company that also own the asset in Kedah State Health Department and the rest is Malaysia Government Ownership. This system is specifically will be used by staff especially technician in Unit ICT to keep track all the asset and head of Unit ICT who is admin will monitor the system and able to generate a report. The problem that Unit ICT faced is they always lost to trace back the asset after the asset has been change the owner. For instance, the owner of the asset has moved to another unit or another section, then the asset such personal computer and the printer also moved to other owner. This is hard to track in order to maintain and upgrade the asset. By proposing this system, it can help technician to trace the owner of the asset by entering a serial number of asset and it can trace who is company that provide the asset in order to return to its company. The system also could generate a report of the asset where it will be easier to admin to know which section and unit lack oflCT asset has so that Unit ICT could provide ifthere is a request of the asset The methodology that was used to develop this proposed system is Rapid ApRlication Development (RAD) methodology, and the data requirement technique that was used is by interview the user and by experienced using the old system.